Colonic Obstruction due to Biliary Calculus: A Rare Case - Dias,Marta Vaz (2024)
Abstract Colic obstruction due to a gallstone impacted at the sigmoid colon is a rare entity. Despite its rarity, the radiologist should be aware of its existence, allowing a prompt diagnosis and treatment. This article describes an 83-year-old male patient with a six-day history of lower quadrant abdominal pain and constipation. In this context an abdominal ultrasound was performed where colonic distension and free interloop fluid was seen. Therefore, a CT was obtained and an impacted gallstone was seen at the sigmoid colon. Removal of the calculus through colonoscopy was attempted but without success, then an exploratory laparotomy was performed, and the calculus was successfully removed.